Acoustical model of vegetal wools including two types of fibers. (1st January 2018) - Piégay, Clément; Glé, Philippe; Gourdon, Emmanuel; Gourlay, Etienne; Marceau, Sandrine
Abstract: In the field of biobased materials, vegetal wools present interesting acoustical properties for insulation and absorption purposes in buildings. These materials are characterized by a large dimensional variability of their natural fibers. Moreover, they often include a proportion of polymer fibers in order to ensure the cohesion of the wools, but that may have an influence on their acoustical performances. However, acoustical models have been specially developed and applied to the case of conventional homogeneous fibrous material having homogeneous fibers. In this paper, to optimize the acoustical performances of vegetal wools, a model taking into account two types of fibers (vegetal and polymer) based on a composite Tarnow approach is proposed. This model has been validated by comparison with experimental measurements on two different vegetal wools (flax and hemp). Finally, the interest of the model in the optimization process of acoustical performances of vegetal wools is estimated thanks to simulations of the sound absorption coefficient for a large range of porosities and vegetal fiber radii.